Association of Chemotherapy Timing in Pregnancy With Congenital Malformation. Issue 12 (December 2021) - van Gerwen, Mathilde; Maggen, Charlotte; Cardonick, Elyce; Verwaaijen, Emma J.; van den Heuvel-Eibrink, Marry; Shmakov, Roman G.; Boere, Ingrid; Gziri, Mina M.; Ottevanger, Petronella B.; Lok, Christianne A. R.; Halaska, Michael; Shao, Long Ting; et al.
Abstract : (Abstracted from JAMA Network Open 2021;4:e2113180) Chemotherapy puts a developing fetus at risk of teratogenic effects. The standard recommendation is that chemotherapy be administered after organogenesis is complete, however, the exact gestational age that chemotherapy can be administered safely and avoid causing congenital malformations remains unknown.